2020
DOI: 10.1097/sla.0000000000004468
|View full text |Cite
|
Sign up to set email alerts
|

Compromised AMPK-PGCIα Axis Exacerbated Steatotic Graft Injury by Dysregulating Mitochondrial Homeostasis in Living Donor Liver Transplantation

Abstract: Objective: To investigate the association of graft steatosis with long-term outcome, and to elucidate the mechanism of steatotic graft injury in adult living donor liver transplantation. Summary of Background Data: The utilization of steatotic graft expands the donor pool for living donor liver transplantation (LDLT). However, it remains controversial due to its high morbidity and mortality. Elucidating the mechanism of steatotic graft injury is crucial to develop therapeutic strategies targeting at graft in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Activation of AMPK increased the phosphorylation of GR at serine-211 and reversed GC-induced hepatic steatosis and suppressed GC-mediated stimulation of glucose production in rats[ 143 ]. Interestingly, impaired AMPK activity was associated with steatotic graft injury in patients with living donor liver transplantation[ 144 ]. Thus, whether AMPK activators can ameliorate the metabolic side effects of GCs in SOT warrants investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK increased the phosphorylation of GR at serine-211 and reversed GC-induced hepatic steatosis and suppressed GC-mediated stimulation of glucose production in rats[ 143 ]. Interestingly, impaired AMPK activity was associated with steatotic graft injury in patients with living donor liver transplantation[ 144 ]. Thus, whether AMPK activators can ameliorate the metabolic side effects of GCs in SOT warrants investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) ameliorated hepatocellular apoptosis mediated by PINK1-dependent mitophagy in hepatic IRI through adenosine monophosphate-activated protein kinase (AMPK)α activation [ 28 ]. This study was echoed by our recent finding, which reported that a compromised AMPK–PGC1α axis exacerbated steatotic graft injury by dysregulating mitochondrial homeostasis through impairment of biogenesis [ 29 ].…”
Section: Acute-phase Inflammation Initiated By Hepatic Irimentioning
confidence: 94%
“…Increased macrovesicular steatosis (>30%) was associated with increased histological damage, hepatic function derangement and reduced survival after liver transplantation according the systemic review [ 43 ]. Moreover, our recent study demonstrated that graft steatosis over 10% was an independent risk factor for poor post-transplant survival and was associated with acute graft injury after living donor liver transplantation (LDLT) [ 29 ]. Along with the mechanism underlying NAFLD being clarified, the mechanisms of severe IRI in steatotic grafts are paid more attention [ 44 ].…”
Section: Acute-phase Inflammation Initiated By Hepatic Irimentioning
confidence: 99%
“…Activation of AMPK increased the phosphorylation of GR at Serine-211 and reversed GC-induced hepatic steatosis and suppressed GCmediated stimulation of glucose production in rats [143] . Interestingly, impaired AMPK activity was associated with steatotic graft injury in patients with living donor liver transplantation [144] . Thus, whether AMPK activators can ameliorate the metabolic side effects of GCs in SOT warrants investigation.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%